Performance of Nellore young bulls on Marandu grass pasture with protein supplementation - Moretti, Matheus Henrique [UNESP]; Resende, Flávio Dutra de [UNESP]; Siqueira, Gustavo Rezende [UNESP]; Roth, Anna Paula de Toledo Piza [UNESP]; Custódio, Letícia; Roth, Marcella de Toledo Piza [UNESP]; Campos, Wellington da Costa de; Ferreira, Luiz Henrique (Sociedade Brasileira de Zootecnia, 2013)
The objective of this study was to verify the effect of low-intake supplementation on performance of Nellore young bulls kept on Marandu grass pasture. The experiment was divided in two periods: the dry and rainy seasons. Treatments during the dry period were composed of mineral salt with urea and mineral supplement enriched with true protein and additive. In the rainy period treatments were mineral salt and enriched mineral supplement only. Pastures were evaluated and animals were weighed in both evaluation phases. The variables studied were evaluated in a completely randomized design in a split-plot arrangement, where plots were treatments and subplots were the periods within each phase, considering the types of supplementation as treatments. During the dry season there was no effect of supplement type in the first and second periods of assessment on weight gain of animals, which was of 0.307 and 0.113 kg/day, respectively. In the third period of this phase there was effect of the type of supplementation on animal performance; animals which received enriched mineral supplement gained 0.600 kg/day vs. 0.517 kg/day for those which received mineral salt with urea. In the rainy season, animals receiving enriched mineral supplement gained more weight than animals receiving mineral supplement: 0.800 and 0.696 kg/day, respectively. Mineral supplementation with addition of protein and additives provides increases in the weight gains of animals kept at a grazing regime of 15%.
Keywords: additive; animal performance; dry season; rainy season; Supplement